Analisis Kesulitan Siswa dalam Mempelajari Bahasa Arab di Kelas VII-6 MTs Budi Agung - Susanti, Desi; Rahma, Ainur; Khairani, Ismi (Indo-MathEdu Intellectuals Journal, 2025)
MTs Budi Agung students find it difficult to learn Arabic, even though learning Arabic is very important. This study aims to identify the difficulties of grade VII students of MTs Budi Agung in learning Arabic and the factors that influence it. This study uses a descriptive qualitative method with observation and interview data collection techniques. This study involved around 30 grade VII-6 students and Arabic teachers as subjects. Data collection techniques were carried out through participant and non-participant observation and structured and unstructured interviews. Data were analyzed using a descriptive qualitative analysis method with theme analysis techniques. The results showed that students had difficulty in understanding sentence structure, vocabulary, and pronunciation due to lack of learning motivation, parental support, and teacher ability and development of Arabic learning strategies. These factors have an impact on low academic achievement and student learning motivation, so that students have difficulty learning. The results of the study suggest that it is necessary to improve teacher skills, develop interactive learning strategies, improve communication between teachers-students-parents, and provide varied learning resources. This study contributes to the development of Arabic language education in Indonesia and can be used as a reference for teachers and schools to improve the quality of Arabic language learning.